Model Sistem Monitoring Perlintasan Kereta Api Menggunakan Arduino Mega - Triyanto, Irfan Rusidy; Djuana, Endang; Gozali, Ferrianto; S, Kuat Rahardjo T; Sunarto, Sunarto (Jurnal Telematika, 2017)
Monitoring system at railway crossing is a system that can be used to monitor train and the railway crossing that will be passed by train. In designing simulation for this monitoring system model, Arduino Mega is needed as a microcontroller. Besides that, radio-frequency identification (RFID) sensor is used to identify the train and ultrasonic sensor is used to detect the train. Data from train and railway crossing will be stored in database. This data that have been stored will be displayed in a server computer. In this display, there will be data from train and the railway crossing. A router is used to send the data to the Internet and an Ethernet module is used to bring the data from Arduino Mega. Experiments were conducted on a model railroad through a computer server. In the test results, the use of features such as train detection of ultrasonic sensors and sensor RFID as the train identification have been tested to work well. The process of sending data from Arduino Mega to be displayed on the display monitor in the server computer is depending on traffic data at the time of testing.Sistem monitoring pada perlintasan kereta api merupakan sistem yang dapat digunakan untuk melakukan deteksi pada kereta dan identifikasi perlintasan yang dilaluinya. Pada perancangan simulasi untuk model sistem monitoring ini, diperlukan Arduino Mega sebagai mikrokontroler dan sensor radio-frequency identification (RFID) dalam proses identifikasi kereta dan  sensor ultrasonik dalam proses deteksi kereta. Data kereta api dan perlintasan disimpan pada sistem basis data. Data yang telah disimpan ditampilkan pada komputer server. Pada tampilan server tersebut, terdapat data kereta dan juga perlintasan. Untuk pengiriman data, dipergunakan router untuk mengirim data ke Internet dan modul Ethernet untuk meneruskan data dari Arduino Mega. Uji coba dilakukan pada model kereta api untuk ditampilkan pada komputer server. Hasil pengujian menunjukkan bahwa dengan menggunakan fitur pendeteksi kereta berupa sensor ultrasonik dan pengidentifikasi kereta berupa sensor RFID, proses identifikasi kereta bekerja dengan baik. Adapun, proses pengiriman data dari Arduino Mega hingga dapat ditampilkan oleh layar monitor komputer server tergantung dari lalu lintas data pada waktu pengujian dilakukan.